Markets and development bulletin (Asian Development Bank, 2007)
Among M4P publications, the Markets and Development Bulletin (MDB) series presents information in a different manner to other publications. It is written in direct language, and highlights particular aspects of research results. The MDB is a relatively short publication of only 4 pages, of which 2 pages contain the presentation of results and 2 pages contain “talking heads” – summarized comments from various relating stakeholders. The inclusion of comments from stakeholders gives the MDB an interesting and topical feel, and allows the presentation of a variety of viewpoints on the subject.